Mono- and dinuclear Ni(i) products formed upon bromide abstraction from the Ni(i) ring-expanded NHC complex [Ni(6-Mes)(PPh3)Br]. Issue 3 (15th December 2017) - Blackaby, William J. M.; Sabater, Sara; Poulten, Rebecca C.; Page, Michael J.; Folli, Andrea; Krewald, Vera; Mahon, Mary F.; Murphy, Damien M.; Richards, Emma; Whittlesey, Michael K.
Abstract : New T- and Y-shaped Ni(i ) complexes are reported and analysed by DFT and EPR. Abstract : Bromide abstraction from the three-coordinate Ni(i ) ring-expanded N-heterocyclic carbene complex [Ni(6-Mes)(PPh3 )Br] (1 ; 6-Mes = 1, 3-bis(2, 4, 6-trimethylphenyl)-3, 4, 5, 6-tetrahydropyrimidin-2-ylidene) with TlPF6 in THF yields the T-shaped cationic solvent complex, [Ni(6-Mes)(PPh3 )(THF)][PF6 ] (2 ), whereas treatment with NaBAr F 4 in Et2 O affords the dimeric Ni(i ) product, [{Ni(6-Mes)(PPh3 )}2 (μ-Br)][BAr F 4 ] (3 ). Both2 and3 act as latent sources of the cation [Ni(6-Mes)(PPh3 )] +, which can be trapped by CO to give [Ni(6-Mes)(PPh3 )(CO)] + (5 ). Addition of [(Et3 Si)2 (μ-H)][B(C6 F5 )4 ] to1 followed by work up in toluene results in the elimination of phosphine as well as halide to afford a co-crystallised mixture of [Ni(6-Mes)(η 2 -C6 H5 Me)][B(C6 F5 )4 ] (4 ), and [6MesH⋯C6 H5 Me][B(C6 F5 )4 ]. Treatment of1 with sodium salts of more strongly coordinating anions leads to substitution products. Thus, NaBH4 yields the neutral, diamagnetic dimer [{Ni(6-Mes)}2 (BH4 )2 ] (6 ), whereas NaBH3 (CN) gives the paramagnetic monomeric cyanotrihydroborate complex [Ni(6-Mes)(PPh3 )(NCBH3 )] (7 ). Treatment of1 with NaO t Bu/NHPh2 affords the three-coordinate Ni(i ) amido species, [Ni(6-Mes)(PPh3 )(NPh2 )] (8 ). The electronic structures of2, 5, 7 and8 have been analysed in comparison to that of previously reported1 using a combination of EPR spectroscopy and density functional theory.